Rancang Bangun Sistem Informasi Pengukuran Tingkat Kepuasan Nasabah Terhadap Pelayanan Program Sahabat Daya Universitas (SDU) Pada PT. BTPN Syariah Menggunakan Metode Servqual & Importance Performance Analysis Gap - Uro Abdulrohim; Herna Gunawan; Sri Handayani Togatorop (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
Competition in the field of banking services in Indonesia is getting faster and tighter. This is what drives PT. Btpn Syariah always strives to provide added value and make a difference in the life of every customer served, in providing good service performance so that btpn creates a program which helps customers to increase knowledge and skills capacity in a measurable and sustainable manner, assistance includes customer capacity. maintain the university's friendship power program (SDU) by measuring the level of satisfaction of customers who have attended the SDU program. Based on the explanation above, it can be concluded that to overcome the problems that occur can be solved using an information system measuring customer satisfaction levels with the Servqual Method. The Servqual method will assist in collecting data taken through questionnaires and analyzing each variable that will be used as a question in the questionnaire. Through this, it will be known what influences customer expectations for the service quality of the SDU program at PT. BTPN Syariah.